2022
DOI: 10.1007/s10549-022-06544-0
|View full text |Cite
|
Sign up to set email alerts
|

Sexual activity and functioning in long-term breast cancer survivors; exploring associated factors in a nationwide survey

Abstract: Purpose Sexual health is a key quality of life issue. Knowledge concerning sexual health in long-term breast cancer survivors (BCSs) is limited. Within a nationwide sample, we aimed to assess the prevalence of sexual inactivity and to explore factors associated with sexual inactivity and reduced sexual functioning among long-term BCSs. Methods Long-term BCSs aged 20–65 years when diagnosed with early-stage breast cancer in 2011–2012 were identified by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 60 publications
3
19
0
1
Order By: Relevance
“…The severe limitations in joint symptoms were in line with those found in postmenopausal women with breast cancer who completed 5 years of AI (FACT-ES questionnaire) 4 . Joint symptoms have also been found as a long-term ET follow-up problem in breast cancer survivors 15 . Moreover, the lack of differences in joint symptoms between age groups (<65 vs >65 y) indicates that these symptoms are not age related.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The severe limitations in joint symptoms were in line with those found in postmenopausal women with breast cancer who completed 5 years of AI (FACT-ES questionnaire) 4 . Joint symptoms have also been found as a long-term ET follow-up problem in breast cancer survivors 15 . Moreover, the lack of differences in joint symptoms between age groups (<65 vs >65 y) indicates that these symptoms are not age related.…”
Section: Discussionsupporting
confidence: 77%
“…4 Joint symptoms have also been found as a long-term ET follow-up problem in breast cancer survivors. 15 Moreover, the lack of differences in joint symptoms between age groups (<65 vs >65 y) indicates that these symptoms are not age related. Moreover, lower joint stiffness scores (QLQ-ELD14) were observed in older patients with a primary tumor at other sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,7,21,22,24,29,57,58] In a recent large cross-sectional study, sleep problems and fatigue were associated with sexual function problems, supporting this hypothesis. [59] We also found that worsening physical function was associated with worsening sexual function during adjuvant endocrine therapy. The link between poor physical function and sexual function problems has previously been reported, although not consistently; however, prior studies were limited by cross-sectional design.…”
Section: Discussionmentioning
confidence: 61%
“…The link between poor physical function and sexual function problems has previously been reported, although not consistently; however, prior studies were limited by cross-sectional design. [17,22,26,59] It is possible that physical function limitations are attributable to joint discomfort in the setting of endocrine therapy, which we hypothesize may, in turn, affect multiple domains on the MOS-SP, such as sexual interest and ability to relax and enjoy sex; however, further study is needed to con rm this association and assess the mechanism by which physical function impairment during endocrine therapy impacts sexual function.…”
Section: Discussionmentioning
confidence: 96%